The Intersection Graph of Subgroups of the Dihedral Group of Order 2pq - Khudhur, Peshawa M.; Haji, Rashad R.; Khasraw, Sanhan M.S. (Iraqi Journal of Science, 2021)
For a finite group G, the intersection graph of G is the graph whose vertex set is the set of all proper non-trivial subgroups of G, where two distinct vertices are adjacent if their intersection is a non-trivial subgroup of G. In this article, we investigate the detour index, eccentric connectivity, and total eccentricity polynomials of the intersection graph of subgroups of the dihedral group for distinct primes . We also find the mean distance of the graph .